Simultaneous Projection and Positioning of Laser Projector Pixels - Kitajima, Yuki (IEEE transactions on visualization and computer graphics, 2017)
This paper presents a novel projected pixel localization principle for online geometric registration in dynamic projection mapping applications. We propose applying a time measurement of a laser projector raster-scanning beam using a photosensor to estimate its position while the projector displays meaningful visual information to human observers. Based on this principle, we develop two types of position estimation techniques. One estimates the position of a projected beam when it directly illuminates a photosensor. The other localizes a beam by measuring the reflection from a retro-reflective marker with the photosensor placed in the optical path of the projector. We conduct system evaluations using prototypes to validate this method as well as to confirm the applicability of our principle. In addition, we discuss the technical limitations of the prototypes based on the evaluation results. Finally, we build several dynamic projection mapping applications to demonstrate the feasibility of our principle